Mining for peaks in lc-hrms datasets using finnee - a case study with exhaled breath condensates from healthy, asthmatic, and copd patients - Erny, Guillaume L. (2020)
This work was financially supported by the projects: (i) UID/ EQU/00511/2019 - Laboratory for Process Engineering, Environment, Biotechnology and Energy − LEPABE funded by national funds through FCT/MCTES (PIDDAC); (ii) POCI-01-0145-FEDER-029702 and POCI-01-0145-FEDER031297 funded by FEDER funds through COMPETE2020 − Programa Operacional Competitividade e Internacionalizaca̧ õ (POCI) and by national funds (PIDDAC) through FCT/ MCTES; (iii) AstraZeneca − Projecto OLDER (CEDOC/ 2015/59); (iv) iNOVA4Health - UID/Multi/04462/2013, financially supported by FCT/Ministerio da Educação e Ciência, and co-funded by FEDER under the PT2020 Partnership Agreement.